(untitled) (Journal of NELTA, 2014)
The English language learning guidebooks (ELLGs), among many other available materials for learning English in Bangladesh, seems to be unique as well as worthy of investigation for they claim to teach English in 30 days. In fact, they are marketed with such discourse that these guidebooks are panacea for learning English without even the assistance of any teacher, text book, or other means. One major point to be marked here is these ELLGs mainly (often solely) focus on the speaking skill and tend to claim that learning the spoken aspect of a language is equivalent to learning the language. Being moved by such anomalous discourses and facts, this qualitative study critically looks at the discourses of ELLGs available in Bangladesh to unveil their actual purpose as well as to be informed about their educational philosophy. The findings suggest that the ELLGs are utterly business oriented products (rather than ELT materials), which instrumentally promote the ‘product approach based traditional form of education’ (Dewey, 1938). DOI: http://dx.doi.org/10.3126/nelta.v18i1-2.10336 Journal of NELTA, Vol 18 No. 1-2, December 2013; 133-147